A comparative analysis of autograft choices of anterior cruciate ligament reconstruction and their effects on muscle strength and joint biomechanics - Wiem Issaoui; Wiem Issaoui; Ismail Dergaa; Ismail Dergaa; Ismail Dergaa; Hatem Ghouili; Abdelfatteh El Omri; Noomen Guelmami; Philippe Chomier; Mourad Ghrairi; Helmi Ben Saad; Helmi Ben Saad; et al. (Frontiers in Sports and Active Living)
IntroductionAnterior cruciate ligament reconstruction (ACLR) is crucial to restore knee stability and function after ACL injuries, especially in physically active individuals. Despite advances in surgical techniques and rehabilitation protocols, the choice of autograft has a significant impact on postoperative recovery, particularly on muscle strength and joint biomechanics. In this study, the effects of four autografts are investigated: Iliotibial band (ITB), combined ITB and hamstring tendon (ITB + HT), hamstring tendon (HT) and bone-tendon-bone (BTB) on quadriceps and hamstring peak torque (QPT and HPT) recovery and hamstring to quadriceps ratio (H:Q) to assess knee stability and function.MethodsForty-two active males (mean ± standard deviation of age: 31.5 ± 6.1 years, height: 177 ± 6 cm, weight: 76 ± 11 kg, body mass index: 24.5 ± 2.2 kg/m²) with primary ACL ruptures were allocated to the four graft groups (ITB: n = 16, ITB + HT: n = 12, HT: n = 7, BTB: n = 7) and underwent a standardized rehabilitation protocol. Quadriceps and hamstring peak torque (QPT and HPT, respectively) as indicators of isokinetic muscle strength were assessed both postoperatively and follow-up after approximately six months (mean 6.29 ± 1.70 months)ResultsSignificant differences in QPT and HPT recovery between the healthy and injured legs were found in all graft groups (P < 0.001). The BTB group showed the largest QPT deficit between healthy and injured legs (Δ = 133.4 Nm, Cohen's d = 8.05) and HPT deficit (Δ = 41.1 Nm, Cohen's d = 4.01). In contrast, the ITB + HT group showed the smallest deficits in QPT (Δ = 22.5 Nm, Cohen's d = 0.73) and HPT (Δ = 13.5 Nm, Cohen's d = 1.21). The BTB group also showed the largest deviation in H:Q ratios (Δ = −0.23, Cohen's d = 2.70), while the HT group showed a more balanced recovery with smaller significant deficits in H:Q ratios (Δ = −0.07, Cohen's d = 0.46).ConclusionThe BTB graft showed the most pronounced variations in QPT and HPT between healthy and injured legs in the short term, indicating the importance of longitudinally monitoring knee stability to determine the best autograft choice for ACLR. While all graft types contribute to muscle strength recovery, the HT graft may provide advantages in balancing muscle strength and potentially enhancing knee stability.